2007
DOI: 10.1002/ptr.2050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toki‐shakuyaku‐san on acetylcholine level and blood flow in dorsal Hippocampus of intact and twice‐repeated ischemic rats

Abstract: The effects of Toki-shakuyaku-san (TSS) ingredients on acetylcholine (ACh) release in the dorsal hippocampus (DH) were investigated in intact and twice-repeated ischemic rats using in vivo microdialysis-HPLC. Moreover, the effect of TSS on blood flow was investigated in intact rats using laser Doppler flowmetry. TSS at 300 mg/kg p.o. increased ACh and blood flow after 40 min in intact rats. TSS also increased ACh in ischemic rats but to a lesser extent than in intact rats. These results could suggest that TSS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…TSS activates cholinergic [1014] and monoaminergic [12, 13, 15] neurons and has a protective effect on amyloid β [16, 17], an antioxidant effect [18, 19], and an antiapoptosis action [12]. Several clinical studies have also suggested that TSS improves cognitive impairment in dementia, MCI, and poststroke patients [20–22].…”
Section: Introductionmentioning
confidence: 99%
“…TSS activates cholinergic [1014] and monoaminergic [12, 13, 15] neurons and has a protective effect on amyloid β [16, 17], an antioxidant effect [18, 19], and an antiapoptosis action [12]. Several clinical studies have also suggested that TSS improves cognitive impairment in dementia, MCI, and poststroke patients [20–22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DSS modulates metabolism of monoamine neurotransmitters including increasing the content of norepinephrine (NE), DA and 5-hydroxytryptamine (5-HT) in brains of aged mice while protecting the cortical ultrastructure [41], which may be the major mechanism of DSS for improving memory dysfunction induced by alcohol. In addition, DSS not only increased ACh and blood flow in intact rats, it also increased ACh in ischemic rats in the dorsal hippocampus (DH), suggesting that DSS can improve the cognition [49].…”
Section: The Effect On the Neurotransmitter And The Central Nervous Smentioning
confidence: 99%
“…A multitude of cellular and molecular mechanisms have been associated with neuroprotection of DSS that include modulation of neurotransmitter, regulation of cerebral blood flow and reduction of NO and malondialdehyde [13,17,19]. In this study, we first reported that DSS improved neuronal outcome through the promotion of angiogenesis and neurogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, its use is extended to brain diseases. For example, Hatip-Al-Khatib et al reported that DSS increased acetylcholine and blood flow in global cerebral ischemia rats [19]. A clinical study also showed that DSS increased regional cerebral blood flow in the posterior circulation in patients with mild cognitive impairment and Alzheimer's disease [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation